Pelatihan Pengolahan Sampah Organik untuk Memberi Nilai Tambah Terhadap Limbah di Padukuhan Bandaran - Muthmainni, Ainun Nafsi; Febrianti, Lidia; Permatasari, Kiki; Fakhriya, Naidan Tsaqif Dwi; Prasetya, Sigit; Hanianjaya, Shaka; Siwi, Pramesti; Benita, Alodia; Syahputra, Raihan Dhimas; Ananta, Muhammad Rifki Agung; Azmawati, Dian (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
The community of Padukuhan Bandaran can now sort waste independently, where the collected waste is transported to the TPST (Integrated Waste Disposal Site). Inorganic waste has its own management, while organic waste has not been processed, so the waste will be disposed of without any further efforts. The community in Padukuhan Bandaran has not been able to utilize organic waste optimally, even though organic waste can be used to be processed into liquid fertilizer or compost. Seeing conditions like this, it not only has an impact on environmental pollution but can also cause health problems for the community. This community service program aims to contribute to efforts to increase knowledge and awareness of environmental cleanliness through the utilization of household waste produced by the community in Padukuhan Bandaran. The method used is to conduct socialization and practice in processing organic waste. The level of community participation, knowledge, and awareness were measured before and after the implementation of the program. The results obtained from the socialization activities showed a significant increase in all aspects observed. The participation aspect showed good results, this was indicated by the participation of 29 people in the socialization activities. The aspect of community knowledge increased, this was indicated by the results of the pre-test and post-test carried out. The aspect of increasing public awareness, this is indicated by the emergence of enthusiasm to try the organic waste processing method of stacked buckets and losida. This program provides a foundation for sustainable waste processing so that a better environment can be created. The sustainability of the program is directed at habituating the community so that this activity can become routine and be emulated by communities in other areas.